Role of Agricultural Products in Foreign Trade of Nepal - Udaya Bahadur Rana Magar (International Journal of Agriculture System, 2019)
Nepal is developing country and it’s economic mainly based on Agricultural sector. A large number of people are relying on agriculture sector. However, still some districts are suffering from food deficit and huge amount of food items import from neighboring countries as well as others countries. In these reason, the Nepalese export import trade is unbalance. In this condition, this paper is trying to identify the role of agriculture sector in foreign trade of Nepal. For these purpose, we have used the secondary data and using the descriptive methods for getting the results. The analysis of data showed that imports of agricultural products are increasing from neighboring country as well as others countries. Two third amounts of agricultural products have imported from India and remaining portion from others countries. Due to large amount of imported agricultural product, Nepalese foreign trade is unbalanced. So policy maker should be focused on development of agriculture field, concerning policy and programs of this sector and pattern of foreign trade should be revised and reformed by the diversification, modernization, instrument-focused agriculture system, which could help to reduce trade deficit and keep it in certain trade balance of Nepal.